Analisis Laporan Sistem Akuntabilitas Kinerja Instasi Pemerintah Terhadap Kinerja Sekretariat DPRD Kabupaten Sikka Tahun 2023 - Daria Evarista Tuku; Antonius Philipus Kurniawan; Yustina Olivia Da Silva (Jurnal Ekonomi Manajemen Akuntansi, 2024)
This study aims to analyze the effect of the implementation of the Government Agency Performance Accountability System (SAKIP) on the performance of the Sikka Regency DPRD Secretariat in 2023. The approach to this study is descriptive qualitative using primary and secondary data. Data were collected through interviews, observations and documentation of SAKIP reports. The results of the study indicate that the implementation of SAKIP has not been fully optimal, especially in terms of collecting performance data and following up on evaluation results as a basis for providing rewards and punishments. This study recommends the development of SOPs for performance measurement and utilization of evaluation results as strategic steps to improve agency accountability and performance.